A Simple Weighing Method for Spherical Cells. (August 2015) - Zhao, Qili; Shirinzadeh, Bijan; Cui, Maosheng; Sun, Mingzhu; Zhao, Xin
This article presents a simple weighing method for spherical cells to avoid the high cost of correlated devices in traditional cell-weighing methods. In this method, the constant falling speeds of the spherical objects in liquid are derived to estimate their masses online. Using this method, the detected density of one type of microbead is highly in accordance with the known value. This method is proved to be capable of detecting tiny variations of the cell mass (at least within 1% of the cell mass). Finally, the proposed method is applied in nuclear transplantation operations, and, for the first time, the proper amount of the removed cytoplasm in porcine enucleation is estimated. The proposed method is able to weigh cells with a success rate of 92% at an average speed of 22 s/cell, and it can be performed on traditional microoperation systems, which makes it easily applicable in biological applications.